Inheritance of tolerance to Cowpea Mild Mottle Virus in soybean - Arias, Carlos A Arrabal; Almeida, Alvaro M R; Mituti, Tatiana; Kitajima, Elliot W (Crop breeding and applied biotechnology, 2015)
Soybean stem necrosis is caused by Cowpea mild mottle virus (CPMMV) and it has been recognized as an emerging and economically important disease in Brazil. No resistant, but only tolerant cultivars have been identified so far, and their genetic control is still unknown. To investigate the inheritance of soybean tolerance to CPMMV, two crosses between tolerant cultivars (BRS 133 x BRSMT Pintado), and between a susceptible (CD 206) and a tolerant cultivar (BRSMT Pintado) were carried out to obtain F2 and F2:3generations. Quantitative and qualitative analyses applied to the data from greenhouse evaluations showed that there are at least two distinct major genes determining tolerance to CPMMV, one in the soybean cultivar BRS 133 and another in the cultivar BRSMT Pintado, with predominance of additive genetic effects and heritability levels that allow for efficient selection based on early generation means. A necrose da haste em soja é causada pelo vírus Cowpea mild mottle virus (CPMMV) e é considerada uma doença emergente e economicamente importante no Brasil. Apenas cultivares tolerantes foram identificadas até o momento, e o controle genético da tolerância permanece desconhecido. Para estudar a herança da tolerância ao CPMMV foram realizados dois cruzamentos para obter as gerações F2 e F2:3, um entre duas cultivares tolerantes (BRS 133 x BRSMT Pintado) e outro entre uma cultivar suscetível (CD 206) e outra tolerante (BRSMT Pintado). Análises qualitativas e quantitativas aplicadas sobre os dados obtidos nas avaliações em casa-de-vegetação mostraram que existem pelo menos dois genes maiores distintos, um na cultivar de soja BRS 133 e outro na cultivar BRSMT Pintado, determinando a tolerância ao CPMMV. Houve predominância de efeitos genéticos aditivos e herdabilidade, que permite a seleção eficiente baseada em médias, mesmo nas primeiras gerações após o cruzamento.